Cranial Vault Remodeling in Children With Ventricular Shunts. Issue 4 (June 2020) - Sinclair, Nicholas; Ordenana, Carlos; Lee, Joan; Onwuzulike, Kaine; Recinos, Violette; Papay, Francis; Rampazzo, Antonio; Bassiri Gharb, Bahar
Abstract : Introduction: Cranial vault surgery in children with ventricular shunts is more complex due to the possible interference of shunt location with surgical planning and increased risk of shunt related complications. The study evaluated the management of ventricular shunts during cranial vault remodeling (CVR) and subsequent outcomes and complications following CVR. Methods: An IRB-approved retrospective chart review was performed including patients who underwent CVR in presence of a ventricular shunt. Measured outcomes were number of shunt revisions following CVR, 30-day complication rate, 3-month complication rate, and post-CVR Whitaker classification. Finally, a review of the literature was performed, and our results were compared to previous reports. Results: Eleven patients met the inclusion criteria. Ventricular shunt was not exposed in 18%; exposed and not revised in 54%; exposed and left on a bone peninsula in 18% and simultaneously exposed and revised in 18%. Two patients experienced complications within 30-days. Three additional patients experienced complications within 3-months. An average of 2.2 shunt revisions per patient were performed following CVR. Whitaker classification was I in 7 patients, II in 1 patient and III in 2 patients. Shunt revision rate for patients undergoing CVR for hydrocephalic macrocephaly was on average of 1.2 and 1.9 for shunt-induced craniosynostosis in literature. Conclusions: Cranial vault abnormalities in the presence of a ventricular shunt can be effectively treated with CVR. The presence of a shunt does not seem to interfere with final head shape. While leaving the shunt unexposed may appear less morbid, shunt related complications can still occur with this approach. Abstract : Supplemental Digital Content is available in the text